2008
DOI: 10.1074/jbc.m800898200
|View full text |Cite
|
Sign up to set email alerts
|

A PY-NLS Nuclear Targeting Signal Is Required for Nuclear Localization and Function of the Saccharomyces cerevisiae mRNA-binding Protein Hrp1

Abstract: Proteins destined for import into the nucleus contain nuclear localization signals (NLSs) that are recognized by import receptors termed karyopherins or importins. Until recently, the only nuclear import sequence that had been well defined and characterized was the classical NLS (cNLS), which is recognized by importin ␣. However, Chook and coworkers (Lee, B. J., Cansizoglu, A. E., Süel, K. E., Louis, T. H., Zhang, Z., and Chook, Y. M. (2006) Cell 126, 543-558) have provided new insight into nuclear targeting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…Using these guidelines, the human proteome was searched and 81 potential cargoes for Kapb2 were identified, (49,50) some of which they demonstrated interact directly with Kapb2 in vitro (35). A follow-up study provided evidence that the PY-NLS motif is conserved in budding yeast in the RNA binding protein, Hrp1 (Table 1), and also that the PY-NLS functions as a nuclear targeting signal in vivo (36).…”
Section: Proline-tyrosine Nls (Py-nls) Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these guidelines, the human proteome was searched and 81 potential cargoes for Kapb2 were identified, (49,50) some of which they demonstrated interact directly with Kapb2 in vitro (35). A follow-up study provided evidence that the PY-NLS motif is conserved in budding yeast in the RNA binding protein, Hrp1 (Table 1), and also that the PY-NLS functions as a nuclear targeting signal in vivo (36).…”
Section: Proline-tyrosine Nls (Py-nls) Sequencesmentioning
confidence: 99%
“…Although cNLS motifs likely mediate the majority of nuclear protein import (36), it is critical to note that there are many additional transport routes facilitated by nonclassical transport pathways. Hence, there are likely many unidentified and undefined NLS motifs that interact with various transport receptors.…”
Section: Classical Nls Sequencesmentioning
confidence: 99%
“…It should be noted that in yeast, only 57% of the nuclear proteins contains a classical NLS (Lange et al, 2007). The remaining 43% of nuclear proteins is thought to pass the nuclear pore complex via alternative mechanisms, like direct interactions with importin b or nucleoporins, nonclassical nuclear targeting signals, or cotransport via interactions with proteins that do contain NLSs, the socalled piggyback mechanism (Ursula Stochaj, 1999;Christophe et al, 2000;Dostie et al, 2000;Cingolani et al, 2002;Xu and Massagué , 2004;Lee et al, 2006;Chuderland et al, 2008;Lange et al, 2008).…”
Section: The CC and Lrr Domains Play Distinct Roles In The Nucleocytomentioning
confidence: 99%
“…Consistent with this hypothesis, we showed that recombinant Nab2-N-F73D does not bind to Mlp1, whereas Nab2-N-F72D is still competent to bind Mlp1, in an in vitro bead binding assay. To assess the impact of amino acid substitutions at Nab2 Phe 72 or Phe 73 on the relative binding affinity of Nab2 for Mlp1, we measured the binding of S-Tag-Mlp1-NBD to GST-Nab2-N mutants F72D, F73D, or F73W at increasing concentrations of S-TagMlp1-NBD in the solid-phase binding assay. We find that the interaction between Nab2-N-F73D and Mlp1-NBD is undetectable in this assay, whereas Mlp1-NBD binds to Nab2-N-F72D with roughly 2-fold lower relative affinity (K d ϳ 2.3 Ϯ 1.1 M) compared with wild-type (Fig.…”
Section: Identification Of a Minimal Nab2-binding Region In Mlp1-mentioning
confidence: 99%